Performing under pressure - Burke, V (Cranfield University School of Management, 2010)
When it comes to achieving success in business, the route to the top is not dissimilar to that taken by elite athletes. Top performers in sport and business understand how to optimise their psychological and physical strengths to cope well under pressure.